Using the Omaha System to determine health problems of urban Syrian immigrants - Ardıç, Aysun; Esin, Melek Nihal; Koç, Şerife; Bayraktar, Bilgenur; Sunal, Nihal (Wiley, 2019)
Objective(s)This study assessed the health problems of Syrian immigrants living in urban areas using the Omaha System. DesignA descriptive and observational study was conducted in Istanbul. SampleThe sample included 51 Syrian immigrant families and 248 Syrian refugees. MeasuresData were collected using the Omaha System-Problem Classification List and a sociodemographic questionnaire. ResultsThe average household size was 6.36; 71% of those over the age of 18 were not employed. Only 8.5% of children aged 0-15 were vaccinated; 15 nursing problems and 46 signs and symptoms were diagnosed using the Problem Classification List scale. Personal care was the most frequently diagnosed problem, followed by Sanitation, Communication with community resources, Mental health, and Residence. ConclusionsHealth and social problems are common Syrian immigrants living in urban areas. The Omaha System-Problem Classification List can be used as a tool by public health nurses to identify health problems encountered by immigrants.
WOS: 000461577100004
PubMed ID: 30467898
Keywords: Health Problems; Omaha System; Problem Classification Scheme; Refugee; Syrians Immigrants